#recovery – creating common ground through visual and textual information shared in the eating disorder recovery community on Instagram - Paulina Bressel (Information Research: An International Electronic Journal)
Introduction. This exploratory study contributes to information practice research, aiming at increasing the understanding of the perspective of individuals in the social setting of a health community by focusing on the common ground created through shared information. The investigation concentrates on individuals sharing health information in an eating disorder recovery community on Instagram.